PENINGKATAN KETERAMPILAN MEMBACA PERMULAAN MENGGUNAKAN POWER POINT DALAM PEMBELAJARAN DARING - Istiyawati Istiyawati; Sunardi Sunardi (Universitas Tribhuwana Tunggadewi, 2021)
The purpose of this study was to improve students' reading skills in the early reading aspect with the help of power points for first grade students at SDN Simokerto VI/139 Surabaya. Power point is made with a unique display accompanied by this animation which is expected to improve students' initial reading skills. The subjects in this study were 28 first grade students with data collection through tests and observations. The research used is PTK with two cycles. The results showed that there were differences in students' reading skills before and after using power point, where the students' skills in the first cycle during the initial introduction using power point obtained 71.4% results, then increased to 87.5% in the second cycle with increasing skills and the activeness of students in pre-reading activities using the help of power point teaching media, which showed an increase of 16.1%.